Development of Smart Charging Strategies for Electric Vehicles in a Campus Area - Yagcitekin, Bunyamin; Uzunoglu, Mehmet; Ocal, Birol; Turan, Eren; Tunc, Ahmet (IEEE, 2013)
Nowadays, electric vehicles (EVs) are expected to become popular together with the development of smart grid technologies. EVs are preferred, since they have low emission and less power consumption. Smart charging management, charging infrastructure and charging stations are among the crucial necessities for widely usage of EVs. Charging strategies are one of the most challenging concerns related to the charging of electric vehicle. In this study, smart charging management strategy is proposed through application of Floyd algorithm, parking space and power capacity control. Proposed strategy considers substation loading data, voltage fluctuation and behavior of drivers and tries to prevent the overloading of transformers. Survey analysis is made among the academic staff and university students in Yildiz Technical University to determine drivers' behaviors. Whole campus areas including the faculty buildings, substations, parking areas are modeled with MATLAB/Simulink. EVs are successfully routed to the most suitable charge point with the developed charging management strategy algorithm. Within the scope of this study, proposed model and obtained results are discussed in detail.
Keywords: electric vehicle; smart grid; smart charging; charging management; floyd algorithm; Computer Science; Engineering